1997
DOI: 10.1177/08959374970110012101
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Influences on Biofilm Development

Abstract: The amounts and types of nutrients in the environment influence the development and final bacterial and chemical composition of biofilms. In oligotrophic environments, organisms respond to nutrient stress by alterations in their cell morphology and cell surfaces, which enhance adherence. Little is known of the responses to stress by bacteria in the animal oral cavity. The environment in the oral cavity is less extreme, and saliva provides a constant source of nutrients. Catabolic cooperation among oral bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 110 publications
1
112
0
4
Order By: Relevance
“…However, bacteria grown under high-nutrient conditions either fail to form biofilms or form loose, floc-like structures at the substratum that are easily disrupted with fluid shear (27,31,68,97). Instead, bacteria tend to form biofilms under low-nutrient or starvation conditions (17,27,97,130). For instance, Dewanti and Wong found that Escherichia coli O157:H7 biofilms developed on stainless steel chipped faster and contained a higher number of adherent cells when grown in low-nutrient media than when grown in tryptic soy broth (36).…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…However, bacteria grown under high-nutrient conditions either fail to form biofilms or form loose, floc-like structures at the substratum that are easily disrupted with fluid shear (27,31,68,97). Instead, bacteria tend to form biofilms under low-nutrient or starvation conditions (17,27,97,130). For instance, Dewanti and Wong found that Escherichia coli O157:H7 biofilms developed on stainless steel chipped faster and contained a higher number of adherent cells when grown in low-nutrient media than when grown in tryptic soy broth (36).…”
Section: Why Attach In the First Place?mentioning
confidence: 99%
“…Por otra parte, estas infecciones son difícil-mente resueltas por el sistema inmune del hospedero; incluso, dicha respuesta es capaz de ocasionar daños en los tejidos en vecindad a las biopelículas [20][21][22][23][24][25][26][27].…”
Section: Discussionunclassified
“…En estas situaciones clínicas, la cirugía apical representa una manera eficaz y efectiva de desorganizar o eliminar a los microorganismos contenidos en estas organizaciones microbianas [14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionunclassified
“…Dental plaque is a complex environment called a biofilm. Nutrition has both direct and indirect effects on the development and composition of plaque biofilm (Boyd & Maddon, 2003): (i) through a direct supply of nutrients (such as sugar) as substrates for energy, nitrogen or carbon for the bacteria; (ii) by having an effect on the production of metabolic by-products from one organism that provides nutrients for other organisms (Bowden & Li, 1997); (iii) through the production of specific polymers by other bacteria and finally (iv) by altering the environment of the biofilm and thereby influencing bacteria to colonise the biofilm. The interaction between nutritional status and the immune response to the bacterial challenge is an underlying factor in the progression of periodontal disease.…”
Section: Periodontal Diseasesmentioning
confidence: 99%